THE SOURCES OF LANGUAGE ANXIETY IN PUBLIC SPEAKING AMONG DAYAKESE STUDENTS IN UNIVERSITY - Nurwanto, Ahmad; Karani, Elanneri; Usadiati, Wahjuningsih (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2020)
This research was done to investigate the sources of language anxiety in public speaking and to find out the students’ ways to reduce their anxiety among Dayakese students of semester 4 class A English Education Study Program in the University of Palangka Raya. open-ended questionnaire, observation, and interview as the main of the data. Twenty one of Dayakese students as participants. They filled out 9 items of questionnaire and interview was done with 6 items related ways to reduce their anxiety. The observation was done related to students behavior while speaking performance. The result from open-ended questionnaire show that most of the students suffered from anxiety in public speaking performance because of the aspects of self-related, lecturer-related, classmates-related, and the material-related. The result of interview show that students had their own ways to reduce their anxiety which are mental and physical. Mentally, they prepared and asked their classmates to help them speak well by giving comments and suggestions. Physically, they did relaxation and be confidence before doing speaking performance. The result of observation participants went blank and lost utterences during speaking performance. Besides that, lower voice, unclear pronounciation, unnecessary movements, and dry mouth were show students behavior during speaking performance.